Diagnostics of K+ and NO3- in sap to determine nutritional status in potato (Solanum tuberosum L. subsp. andigena) - Gómez S., Manuel Iván; Magnitskiy, Stanislav; Rodríguez, Luis Ernesto (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2017)
Sap analysis is a nutritional diagnostic tool to provide timely fertilization adjustments in crops. The objective of this study was to determine the reference levels of NO3 - and K+ in sap per phenological stage. The study evaluated the proper use of this nutritional diagnostic tool for N and K in Diacol Capiro and Pastusa Suprema potato on the Bogotá Plateau at 55, 75, 100, 125 and 150 days after sowing (das) in response to balanced fertilizer levels (0; 1,450; 1,900 and 2,375 kg ha-1) on the yield, dry matter and harvest index to determine levels for cultivation and phenology. The highest K+ concentration in sap in the stems occurred at the vegetative stage with 4,800-5,000 mg L-1, decreasing in tuberization with 2,725 mg L-1, without significant differences between cultivars; contrary to the behavior of N-NO3 - in the stems, where the maximum concentration at tuberization was 2,466 mg L-1 Capiro and 2,200 mg L-1 Supreme, with decreased values at physiological maturity. The reference levels were obtained at flowering stage for Capiro by quadratic adjustment of N-NO3 - and K+ in sap with 3,280 mg L-1 and 1,231 mg L-1, respectively, and related with the response to fertilization, yield, dry matter, and leaf area. In contrast for Supreme, the evaluated N, with levels higher than 1,250 mg N-NO3 - L-1 in sap, supposed luxury consumption. Using this diagnostic tool in the field, adjustments can be made to the management of nitrogen and potassium nutrition of these cultivars.